Pengaruh Dimensi Kualitas Pelayanan (SERVQUAL) terhadap Kepuasan Pasien - Amalia Fauzana Wijaya; Anastasya Muna Riad; Yusika Br. Purba (Jurnal Keperawatan Florence Nightingale, 2026)
This study aims to analyze the influence of service quality dimensions (Service Quality/Servqual), namely tangibles, reliability, responsiveness, assurance, and empathy, on patient satisfaction at a Primary Clinic. This study employed a quantitative approach with an associative research design. The sample consisted of 62 respondents selected using the accidental sampling technique. Data were collected through questionnaires using a Likert scale that had been tested for validity and reliability. Data analysis was conducted using the Kolmogorov-Smirnov normality test and Spearman Rank Correlation for hypothesis testing because the data were not normally distributed. The results showed that all service quality dimensions had a positive and significant influence on patient satisfaction. This was indicated by highly significant values across all dimensions (Sig. = 0.000; p < 0.001), with a strong level of influence. The responsiveness dimension had the strongest influence on patient satisfaction (ρ = 0.775), followed by assurance (ρ = 0.757), reliability (ρ = 0.720), empathy (ρ = 0.703), and tangibles (ρ = 0.678). In addition, overall service quality demonstrated a very strong influence on patient satisfaction (ρ = 0.816; Sig. = 0.000; p < 0.001). These findings indicate that promptness and responsiveness in service delivery are the most important factors in enhancing patient satisfaction at the Primary Clinic.